2017
DOI: 10.1111/1471-0528.15034
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy weight gain by gestational age and stillbirth: a population‐based cohort study

Abstract: ObjectiveTo study the association between total and early pregnancy (<22 completed weeks) weight gain and risk of stillbirth, stratified by early‐pregnancy body mass index (BMI).DesignPopulation‐based cohort study.SettingStockholm‐Gotland Region, Sweden.PopulationPregnant women with singleton births (n = 160 560).MethodsPregnancy weight gain was standardised into gestational age‐specific z‐scores. For analyses of total pregnancy weight gain, a matched design with an incidence density sampling approach was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…This method ensured that the weight gain of women who experience adverse pregnancy outcomes would be compared with the weight gain of women without adverse outcomes at the same point in pregnancy. 14 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method ensured that the weight gain of women who experience adverse pregnancy outcomes would be compared with the weight gain of women without adverse outcomes at the same point in pregnancy. 14 21 …”
Section: Discussionmentioning
confidence: 99%
“…Subjects were excluded if: (1) weight in early pregnancy <30 kg or >350 kg or (2) z-score of GWG <−4.0 or >4.0, the methods used in the study were similar to the study conducted by Johansson et al . 14 Women with pre-existing medical conditions such as pregestational diabetes, hypothyroidism or hyperthyroidism (affecting GWG) 15 and heart/liver/kidney diseases were also excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent population-based study of pregnancy weight gain and stillbirth in 160 560 deliveries in Sweden, we found that the measurement-to-delivery interval is systematically shorter among deliveries at younger gestational ages (when adverse outcomes such as stillbirths are more likely to occur) than among term deliveries. 4 Unpublished analyses from our cohort from Magee-Women’s Hospital in Pittsburgh, PA, 5 suggests similar general trends, although the magnitude of the difference appears smaller.…”
mentioning
confidence: 66%
“…For example, in the Swedish cohort analysis, we altered the research plan to use a nested case-control design, where weight measurements for controls were drawn from the cohort of ongoing pregnancies at the time of each stillbirth and matched based on the interval between delivery and last measured weight of the stillbirth (which was then used in subsequent analyses). 4…”
mentioning
confidence: 99%